(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
This research paper investigates the impact of child labour on school attendance and academic performance of pupils in public primary schools in the Union Territory (UT) of Jammu and Kashmir, with a specific focus on rural areas. The study explores the extent to which child labour affects educational outcomes, identifies the socio-economic factors contributing to child labour, and discusses the implications for educational policies. Data was collected from multiple rural regions within the state, and both quantitative and qualitative analyses were conducted to assess the correlation between child labour and educational outcomes. The findings indicate a significant negative impact of child labour on both school attendance and academic performance, with rural areas being particularly affected.